Risk and protective factors of alcohol misuse : in the New Zealand defence force : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Albany, New Zealand - Harris, Julia Iringa (Massey University, 2024)
This study contributes to the scientific literature and is committed to increasing the knowledge of the risk and protective factors for alcohol misuse within a sample group of New Zealand Defence Force (NZDF) personnel. The present study investigated these factors from a New Zealand perspective, as existing literature is predominantly centred around the United States and British Forces. This study utilised data from NZDF military personnel who completed a Health and Wellbeing Survey at two time points: 1) in 2016 and 2) in 2019. Potential risk and protective factors were analysed using t-tests, ANCOVA tests, hierarchical regression, and moderation analyses. Several key findings were obtained. First, demographic variables such as male gender, single relationship status, Navy service, Junior Non Commissioned Officer (NCO) rank, younger age, and minority ethnic status were associated with greater alcohol use. In addition, psychological distress and trauma exposure at Time 1 were associated with alcohol misuse at Time 1, and PTS and loneliness at Time 1 predicted alcohol misuse at Time 2. The study also revealed direct associations between social support, unit cohesion, and alcohol misuse. Moderation analyses revealed that social support, leadership perception, and unit cohesion exacerbated the association between psychological distress and alcohol misuse. Similarly, moderation analysis revealed that resilience exacerbated the association between trauma exposure and alcohol misuse. The study underscores the importance of targeting alcohol misuse, as participants appear to be using alcohol to cope; therefore, prevention and intervention efforts should prioritise mitigating trauma exposure, PTS, loneliness, and psychological distress alongside initiatives to enhance adaptive coping among NZDF personnel.
Keywords: 520304 Health psychology